2021
DOI: 10.1039/d0ra08836f
|View full text |Cite
|
Sign up to set email alerts
|

Ecological HPLC method for analyzing an antidiabetic drug in real rat plasma samples and studying the effects of concurrently administered fenugreek extract on its pharmacokinetics

Abstract: The combination of fenugreek extract and metformin can be considered as an auspicious treatment for satisfactory diabetes control and minimizing the expected long-term complications of metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A rat animal model was recently used to compare the pharmacokinetics of metformin, a first-line anti-diabetic drug, with and without the concomitant administration of fenugreek extract. According to the findings, taking fenugreek and metformin at the same time boosted the metformin bioavailability and reduced the drug distribution volume by 70% [ 23 ]. The researcher concluded that this combination could be a useful way to control the blood sugar levels in diabetic patients.…”
Section: Pharmacological Uses Of T Foenum-graecummentioning
confidence: 99%
“…A rat animal model was recently used to compare the pharmacokinetics of metformin, a first-line anti-diabetic drug, with and without the concomitant administration of fenugreek extract. According to the findings, taking fenugreek and metformin at the same time boosted the metformin bioavailability and reduced the drug distribution volume by 70% [ 23 ]. The researcher concluded that this combination could be a useful way to control the blood sugar levels in diabetic patients.…”
Section: Pharmacological Uses Of T Foenum-graecummentioning
confidence: 99%
“…Various criteria are currently utilized to evaluate the environmental impact of various analytical methodologies, however, multi-criteria decision analysis (MCDA) allows for a rating of available analytical methods based on many evaluation criteria at the same time. The Analytical GREEnness (AGREE) [43] calculator is a comprehensive, adaptable, and clear approach to assessing the greenness of analytical procedures. It is based on 12 green chemistry principles.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent drugs include di-peptidyl peptidase 4 inhibitors and sodium glucose co transporter 2 inhibitors (SGLT2) which have been approved after several characterization methods [2]. Previously, large number of drugs with different backgrounds such as anti-cancer and anti-neurological has been employed bioanalytical method for the successful estimation and quantification from different naturally occurring compounds [3,4]. Analytical chemistry and pharmaceutical analysis is the art of determining the composition of the target drug.…”
Section: Introductionmentioning
confidence: 99%